Vaccination of household chickens results in a shift in young children’s diet and improves child growth in rural Kenya - Otiang, E.; Yoder, J.; Manian, S.; Campbell, Zoë A.; Thumbi, Samuel M.; Njagi, L.W.; Nyaga, P.N.; Palmer, G.H. (National Academy of Sciences, 2022)
Childhood growth faltering remains unacceptably high in sub-Saharan Africa. Rural communities dependent on household food production with limited off-farm income or liquid assets to bridge seasonal food availability are especially vulnerable. A cross-sectional survey in Siaya County, Kenya identified 23.5 and 4.8% of children under 5 y of age as stunted and wasted, respectively, using height-for-age Z (HAZ) scores to detect stunting and weight-for-height Z (WHZ) scores for wasting. Although these households are classified as living in poverty or extreme poverty with very limited off-farm income, households commonly have on-farm resources that could be developed to improve nutrition. While 95% of these households have chickens and consumption of eggs was shown to increase childhood growth by an average of 5%, the average flock size is small and constrained by high mortality due to infectious disease. We hypothesized that interventions to relieve this constraint would translate into household decisions influencing the diets and growth of children. Here, we show that vaccination of chickens against Newcastle disease has a causal impact on children’s consumption of animal source foods rich in protein and micronutrients relative to a high-carbohydrate, grain-based diet. Children in treatment households (chicken vaccination) showed overall increases in scores for both HAZ and WHZ relative to control households, benefiting both girls and boys. The findings demonstrate the impact of directing interventions at common on-farm assets managed by women in rural communities and support programs to enhance productivity at the household level.